Continuous and emerging challenges of silver scurf disease in potato. Issue 1 (25th November 2021) - Tiwari, Rahul Kumar; Kumar, Ravinder; Sharma, Sanjeev; Naga, Kailash Chandra; Subhash, S; Sagar, Vinay
Abstract: Potato is regarded as the future crop for assuring food security in the developing world. Of many diseases which limit the growth and trade value of potatoes, silver scurf is emerging at an alarming rate. Potato silver scurf is a widespread disease in which silvery skin blemishes appear on the periderm of tubers. The causal agent Helminthosporium solani Durieu & Mont is an Ascomycete fungus which attacks the potato plants in the field as well as in storage. The pathogen is reported to have a hemibiotrophic or necrotrophic lifestyle. The disease which was earlier considered of minor importance has become a major cause of non-acceptance of commercial potatoes during the last two decades. Lack of resistant cultivars and emergence of thiabendazole fungicide resistant strains has made it much more devastating in potato cultivation and trade. Several new fungicide molecules have been found very effective as seed treatment chemicals in mitigating this disease. Likewise, many beneficial microbial antagonists have shown mycoparsitism and antibiosis against this pathogen. These bioagents can be utilized in an integrated disease management program. Germplasm screening for disease resistance is an important aspect that will assist the resistance breeding program for the development of silver scurf resistant potato cultivars. The pathogen has multiple cell wall degrading enzymes and several genes in glucoside hydrolase family which suggest that there is a need to reconsider the life cycle of this pathogen with special emphasis on its host range. This review draws attention to the pathogenomics, infection process and management possibilities of silver scurf disease and proposes some critical questions to be addressed in the future.